Ochrana předmětů duševního vlastnictví v souvislosti s podnikáním - Sýkora, Pavel (2006)
The title and the topic of this diploma thesis is Protection of Intellectual Property in Relation to Undertaking. The basic goal of the thesis is to analyze the usage of intellectual property objects (intangible goods) in undertaking and decide whether the existing protection level of their holders is satisfactory. To reach this goal, it is necessary to examine the existing legal regulation first and describe it. Major part of this thesis is devoted to this task. The first chapter starts with definitions of terms. The term intellectual property and its relation to other property are examined. The author concludes that although the law treats the intangible goods in some aspects as eternal and ubiquitous, an intangible good can exist only on a data carrier and can be destroyed. The author tries to identify the core differences between ownership of tangible and intangible goods, and briefly discusses the role of intangible goods in undertaking. Follows an overview of reasons for intellec.